Implementation of metacognitive reading strategies to improve English reading ability: a systematic review - Kan, Tang; Noordin, Nooreen; Ismail, Lilliati (Society for Research and Knowledge Management, 2024)
Proficiency in English reading is crucial for overall language competency, as learning relies heavily on written materials. In recent years, experts and scholars have started to regard learning and employing metacognitive reading strategies as an important method for improving English reading comprehension. This systematic review investigated the application of metacognitive reading strategies for enhancing English language reading comprehension ability. This analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. By using certain search keywords, a total of 20 articles concerning the implementation of metacognitive reading strategies for improving English reading comprehension ability were identified from databases that included Scopus, Science Direct, Web of Science, Academic Search Complete, and the Education Resources Information Center. The synthesis of findings indicate a prevalent use of the Metacognitive Awareness of Reading Strategies Inventory and its revised editions, along with a notable emphasis on problem-solving strategies. Moreover, this systematic review highlights the positive effect of metacognitive reading strategies for improving English language reading comprehension ability. Additionally, the study offers pedagogical recommendations for teachers teaching English as a foreign or second language.